(untitled) (Research, Society and Development, 2025)
The use of pesticides in agriculture is essential for controlling pests and diseases, enhancing productivity, and supporting food security. However, their improper and indiscriminate use raises concerns about impacts on the health of producers, consumers, and the environment. The growing use of pesticides in horticulture presents a serious challenge to protecting farmers. This study aimed to assess the risks of pesticide toxicity in vegetable production in Boane District, located in Maputo Province, Mozambique. Semi-structured interviews were conducted with 53 producers using purposive non-probability sampling, along with direct observation. The results showed that the most commonly used pesticides were Mancozeb, Cypermethrin, Abamectin, and Methamidophos. According to the World Health Organization, these range from moderately to extremely toxic. Most producers had not received proper training in safe pesticide handling and did not use the required personal protective equipment (PPE). Additionally, poor understanding of correct dosages and the health risks of exposure puts both producers and consumers at risk of poisoning. The study highlights the urgent need for training and awareness programs focused on safe agricultural practices. It also recommends public policies to protect farmers’ health and ensure food safety for the population.